RELATIONSHIP BETWEEN COMMUNITY-BASED TOTAL SANITATION AND STUNTING IN TODDLERS - Diah Ayu Safira; Avicena Sakufa Marsanti; Pipid Ari Wibowo (Jurnal Delima Harapan, 2023)
Stunting is a chronic nutritional problem that occurs in toddlers characterized by height that is not in accordance with their age. The incidence of stunting in the Kwadungan Health Center Working Area in 2021 was 11.6%. The purpose of this study was to analyze the relationship between the implementation of community-based total sanitation pillar 3 with the incidence of stunting in the Kwadungan Health Center Work Area. This type of research is a quantitative research with a case control research design. With a population of 129 cases and a sample of 72 respondents with 36 cases and 36 controls. The sampling technique used is proportional random sampling technique. Analysis of the data used is the Chi Square test. The results of the Chi Square test showed that there was a relationship between CTPS (0.007), drinking water and household food management behavior and the incidence of stunting with a p value of 0.007 <0.05. The conclusion of this study is that there is a relationship between the management of drinking water and household food with the incidence of stunting. Educational activities such as socialization related to stunting prevention in the Kwadungan Health Center Work Area can be applied to minimize the occurrence of stunting.